Prenatal chlorpyrifos leads to autism-like deficits in C57Bl6/J mice - Anat Lan; Michal Kalimian; Benjamin Amram; Ora Kofman (BMC, 2017)
Abstract Background Children are at daily risk for exposure to organophosphate insecticides, of which the most common is chlorpyrifos (CPF). Exposure of pregnant women to CPF was linked to decreased birth weight, abnormal reflexes, reduction in IQ, as well as increased maternal reports of signs of pervasive developmental disorder. The aim of current study was to examine the long term effects of prenatal exposure to CPF in C57BL/6 J (B6) mice with specific focus on social and repetitive behavior. Methods B6 female mice were treated with vehicle, 2.5 mg/kg CPF or 5 mg/kg of CPF on gestational days 12-15 by oral gavage. On postnatal days (PND's) 6-12 early development and neuromotor ability were assessed by measuring 3 neonatal reflexes in the offspring. In adulthood, PND 90, social behavior was investigated using the social preference, social novelty and social conditioned place preference tasks. Object recognition and restricted interest, measured by the repetitive novel object contact task (RNOC), were also assessed on PN D 90. In order to rule out the possibility that CPF administration induced alterations in maternal care, the dams' behavior was evaluated via the maternal retrieval task. Results CPF treatment resulted in delayed development of neonatal reflexes on PND's 6-12. On PND 90, mice treated prenatally with the 5.0 mg/kg dose exhibited reduced preference towards an unfamiliar conspecific in the social preference test and reduced social conditioned place preference. In the RNOC task, mice exposed prenatally to 2.5 mg/kg dose of CPF showed enhanced restricted interest. CPF administration did not impair dams' behavior and did not cause memory or recognition deficit as was observed in the object recognition task. Conclusions Our data indicate that gestational exposure to CPF has long-term deleterious effects on social behavior and limits exploration of novel objects.